2005
DOI: 10.3725/jjn1993.35.1_1
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in pathogenicity of Meloidogyne incognitapopulations on sweetpotato in Kyushu Okinawa, Japan

Abstract: Regional variation in pathogenicity of Meloidogyne incognita populations on sweetpotato in Kyushu Okinawa, Japan. Zen-ichi San& and Hideaki Iwahori2To use resistant cultivars of sweetpotato effectively occurrence and distribution of pathogenic races of M incognita were examined. Five sweetpotato differential cultivars, 'Norin -1' ,'Norin-2','Tanegashimamurasaki-7','Elegant Summer' and Tred', which were selected from major Japanese sweetpotato cultivars based on resistance response to four M incognita populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…In Japan, M. incognita can be found in most areas, including Kyusyu and Kanto, in which sweetpotato is cultivated 12–14 . Previous studies have reported that at least nine races of M. incognita (SP1–SP9) exist in Japan, and certain races are dominant in specific regions 15 . For example, the SP1 race is predominant in the Kumamoto, Nagasaki, and Saga Prefectures (Kyushu); in contrast, the SP4 and SP6 races are predominant in the Okinawa islands 15 and are found in the Ibaraki and Chiba Prefectures (Kanto) 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, M. incognita can be found in most areas, including Kyusyu and Kanto, in which sweetpotato is cultivated 12–14 . Previous studies have reported that at least nine races of M. incognita (SP1–SP9) exist in Japan, and certain races are dominant in specific regions 15 . For example, the SP1 race is predominant in the Kumamoto, Nagasaki, and Saga Prefectures (Kyushu); in contrast, the SP4 and SP6 races are predominant in the Okinawa islands 15 and are found in the Ibaraki and Chiba Prefectures (Kanto) 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Each race has different pathogenicity to sweet potato cultivars bred in Japan (Sano and Iwahori, 2005). Each population was propagated for two to three months on tomato variety Pritz in pots under the greenhouse condition described below.…”
Section: Greenhouse Testmentioning
confidence: 99%
“…M. incognita has many races (Sano & Iwahori 2005, Tabuchi et al 2017) that are identified based on their differing pathogenicity to several sweet potato cultivars. This has been investigated in Japanese cultivars (Sano et al 2002, Tabuchi et al 2015.…”
Section: Suppression Effects On Nematode Population Density Caused Bymentioning
confidence: 99%
“…This has been investigated in Japanese cultivars (Sano et al 2002, Tabuchi et al 2015. SP2 is a dominant race in Miyazaki and Kagoshima prefectures in the southern area of Kyushu (Sano & Iwahori 2005). Some new cultivars have recently been found to exhibit a strong resistance to SP2 by evaluating the number of egg masses (Tabuchi et al 2015).…”
Section: Suppression Effects On Nematode Population Density Caused Bymentioning
confidence: 99%
See 1 more Smart Citation